Restorative Justice Dan Diversi Dalam Penanganan Jarimah Pelecehan Seksual Berdasar Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat - Abdul Gafur; Ahmadi Hasan; Masyithah Umar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2023)
Abstract: This research discusses the concepts of Restorative Justice and Diversi in the context of the criminal offense of sexual harassment regulated by the Aceh Qanun Number 6 of 2014 on Islamic Criminal Law (Hukum Jinayat). The study employs a literature review and an empirical normative approach based on cases handled by the author. In the realm of Islamic criminal law in Indonesia, there exists the Hukum Jinayat system specifically applicable in Aceh Province under Laws Number 44 of 1999 and Number 11 of 2006. This system governs Jarimah (prohibited acts according to Islamic law) punishable by 'Uqubat (punishment). 'Uqubat encompasses 'Uqubat Utama (such as whipping, fines, imprisonment, and restitution) and 'Uqubat Tambahan (like marriage annulment, revocation of rights). However, in handling cases of sexual harassment under these laws, the implementation of Restorative Justice and Diversi often faces obstacles such as prolonged trauma for the victim, enduring shame, resistance to peace settlements by the victim’s family seeking severe punishment for the perpetrator, and the victim’s family’s desire to distance the perpetrator from their community. This study aims to explore the scope, involved parties, and challenges in executing Restorative Justice and Diversi concerning cases of sexual harassment in accordance with Aceh Qanun Number 6 of 2014 on Jinayat. The conclusion of this research is expected to offer a deeper understanding of efforts to address cases of sexual harassment using the Restorative Justice and Diversi approach within the context of Islamic criminal law in Aceh. Keywords: Restorative, Justice, diversi, harassment, sexual, law Abstrak: Penelitian ini membahas konsep Restorative Justice dan Diversi dalam konteks jarimah pelecehan seksual yang diatur oleh Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat. Penelitian ini dilakukan dengan menggunakan pendekatan studi literatur dan pendekatan normatif empiris dengan kasus yang pernah ditangani penulis sendiri. Dalam konteks hukum pidana Islam di Indonesia, terdapat sistem Hukum Jinayat yang khusus berlaku di Provinsi Aceh berdasarkan Undang-Undang Nomor 44 Tahun 1999 dan Undang-Undang Nomor 11 Tahun 2006. Hukum Jinayat ini mengatur tentang Jarimah (perbuatan terlarang menurut Syariat Islam) yang diancam dengan 'Uqubat (hukuman). 'Uqubat terbagi menjadi 'Uqubat Utama (seperti Cambuk, Denda, Penjara, Restitusi) dan 'Uqubat Tambahan (seperti Pemutusan Perkawinan, Pencabutan Hak). Namun, dalam penanganan jarimah pelecehan seksual, implementasi Restorative Justice dan Diversi seringkali menghadapi hambatan, seperti trauma yang berkepanjangan bagi korban, rasa malu yang berkepanjangan, penolakan perdamaian oleh keluarga korban yang menginginkan hukuman berat bagi pelaku, dan keinginan keluarga korban untuk menjauhkan pelaku dari komunitas mereka.Penelitian ini akan mengeksplorasi ruang lingkup, pihak yang terlibat, serta problematika pelaksanaan Restorative Justice dan Diversi dalam kasus pelecehan seksual sesuai dengan Qanun Aceh Nomor 6 Tahun 2014 tentang Jinayat. Kesimpulan dari penelitian ini diharapkan dapat memberikan pemahaman yang lebih mendalam mengenai upaya penanganan jarimah pelecehan seksual dengan pendekatan Restorative Justice dan Diversi dalam konteks hukum pidana Islam di Aceh. Kata Kunci: Restorative, Justice, diversi, pelecehan, seksual, hukum